Learning Numeracy around School Environment Supported by Mobile Math Trails using Problem-Based Learning Model - Nurin, Nazzun Sholikha; Junaedi, Iwan; Nur Cahyono, Adi (Mathematics Education Journal, 2024)
This study explores how integrating Mobile Math Trails within the Problem-Based Learning (PBL) model can effectively support numeracy learning. This research was conducted using a design research method with an exploratory approach focused on the design experiment stage. The study involved eighth-grade students from SMP N 39 Semarang. Data was collected through observation, questionnaires, portfolios of students’ work, and interviews. The findings show that Mobile Math Trails-supported learning using PBL model can be an alternative numeracy reinforcement learning. The tasks design students explore around the school environment refers to numeracy indicators with specific content, context, and cognitive levels. The features embedded within the Mobile Math Trails application assist students in the problem-solving process. The tasks designed within the application foster a direct link between mathematical concepts and real-world scenarios within the school environment, thereby necessitating students' reasoning skills. Active student involvement is crucial in this learning, as collaboration among peers is essential for generating optimal learning experiences. Moreover, the learning steps outlined in the research necessitate students' physical engagement. Future studies could explore the application of numeracy reinforcement learning facilitated by Mobile Math Trails in diverse environments.